Assessment of coastal erosion related to wind characteristics in peninsular Malaysia - Noram Irwan, Ramli; Ramesh, Yanalagaran (Taylor's University, 2018)
Malaysia is a maritime country that is located north of the Equator. Hence, it is prone to monsoon changes all the time. Monsoon in Malaysia has contributed to a lot of wind-related disaster. Currently, the most alarming wind-related disaster would be coastal erosion. Although it is a natural phenomenon mainly caused by wave motion, the source of wave power is highly dependent on wind characteristic. This wind induced disaster has caused extensive financial loss and destruction of environment. Hence, this study was conducted to investigate the relationship between wind and coastal erosion in Peninsular Malaysia. The eroded locations were gathered by extensive review from prime media and mass media. They were analysed from the year 1984 to 2016 by using image layering technique. The changes in shoreline orientation were determined by observing the changes of the shoreline at a specific area. The wind directional distribution diagram was created using the data from the nearest meteorological station. Both of these parameters were compared and analysed. The result from the empirical investigation shows a good agreement between wind direction and shoreline orientation. Therefore, the shoreline orientation is highly influenced by the changes of wind characterization.